Preliminary study of development mobile application for Kuala Lumpur homeless distribution / Nur Liyana Rosman - Rosman, Nur Liyana (2019)
Homeless according to Sabine Springer, or known also as houseless based on their research, homeless are defined as those who sleeping rough or using public or private shelters to go through their everyday life. In Kuala Lumpur, the exact numbers of homeless person is still unknown. Thus, the goal of this research is to study about the demographic data of the homeless in Kuala Lumpur. Kuala Lumpur had been chosen as the study area because Kuala Lumpur had been the capital city of Malaysia since independent day. But due to the rose numbers of homeless, this problem need to be overcome. Certain type of data that can be acquired from the JKM and NGOs such as year, gender, age and ethnic. Due to the lacks data stored at JKM and Ngo such as the real numbers of homeless or the hotspot location of the homeless, the idea to develop mobile application had come about. The distribution location of the homeless data later is mapped into a hotspot map based on the demographic data by using Arcgis online software. Android studio is used for developing a prototype of mobile application for user to update the real-time data of homeless in Kuala Lumpur. The purpose of the prototype of mobile application is to gather the data of the homeless then the data later can be used by JKM and NGOs for goodness. The development of the mobile application is something new in Malaysia but it still can be one of the way to overcome the problem that have been faced by the related agencies.